Downregulation of S100A9 Reverses Cisplatin-Resistance and Inhibits Proliferation and Migration in Hypopharyngeal Carcinoma. (29th August 2022) - Zeng, Shiyu; Tan, Guolin; Wang, Tiansheng; Wang, Xianyao; Zhou, Zheng; Xiao, Jian; Li, Tieqi; Zhang, Gehou; Li, Wei
Abstract : Purpose . Patients with hypopharyngeal carcinoma (HPC) often progress to an advanced clinical stage at diagnosis. Cisplatin has been widely used in first-line chemotherapy for advanced HPC. However, acquired chemotherapeutic resistance leads to recurrence, metastasis, and a poor survival rate. Therefore, identifying new drug targets to improve treatment effects is still in need. Methods . To screen the differential expression genes (DEGs) and proteins (DEPs), we conducted transcriptomic and proteomic analysis on cisplatin-sensitive cell lines (FaDu) and cisplatin-resistant cell lines (FaDu/DDP) of hypopharyngeal carcinoma. DEGs and DEPs, possibly the most associated with cisplatin-resistance, were verified by real-time polymerase chain reaction (RT-PCR) and western blot (WB), respectively, and the biological function of the screened S100A9 was further tested by CCK8, wound healing, and transwell assays. Results . We identified S100A9 as a target for resensitizing the response to cisplatin in an acquired resistance model. S100A9 overexpression was significantly related to cisplatin resistance. Functional studies in vitro models demonstrated that downregulation of S100A9 overcame cisplatin-resistance and inhibited proliferation and migration. Later, we verified that downregulation of S100A9 suppressed the interleukin-6 (IL6) expression and epithelial-mesenchymal transition (EMT) pathway. Conclusion . In all, S100A9 plays a crucial role in cisplatin-resistance, proliferation, and migration of HPC. Targeting S100A9 may become a novel strategy for the treatment of HPC.